2021
DOI: 10.1177/03635465211017514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-term Radiographic Outcomes and Rate and Time for Conversion to Total Knee Arthroplasty Between Repair and Meniscectomy for Medial Meniscus Posterior Root Tears: A Systematic Review and Meta-analysis

Abstract: Background: Previous meta-analyses have demonstrated superior outcomes in patients undergoing arthroscopic repair of medial meniscus posterior root tears (MMPRTs) compared with meniscectomy. However, these analyses have considered only short- or midterm outcomes and low-quality evidence. Purpose: To compare the mid- to long-term rates of radiographic osteoarthritis (OA) between repair and meniscectomy for MMPRT. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: PubMed, EMBASE, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 43 publications
1
38
0
2
Order By: Relevance
“…Today, the preference for meniscus repair over meniscectomy is well established (9). Evidence suggests that non-degenerative meniscal tears are best repaired using knee arthroscopy, especially in young and active people (10).…”
Section: Meniscal Injuriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, the preference for meniscus repair over meniscectomy is well established (9). Evidence suggests that non-degenerative meniscal tears are best repaired using knee arthroscopy, especially in young and active people (10).…”
Section: Meniscal Injuriesmentioning
confidence: 99%
“…Today, the preference for meniscus repair over meniscectomy is well established ( 9 ). Evidence suggests that non-degenerative meniscal tears are best repaired using knee arthroscopy, especially in young and active people ( 10 ). A recent study has demonstrated that compared to meniscectomy, meniscus repair causes lower rates of degenerative changes and reduces demand for knee replacement in the future ( 10 ).…”
Section: Meniscal Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studies indicated that surgical treatment should be recommended to patients with high requirements and no to low-grade osteoarthritis [4,5]. Currently, there are several surgical options for the treatment of meniscus root tears, like meniscectomy, meniscal repair, and meniscus root reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several surgical options for the treatment of meniscus root tears, like meniscectomy, meniscal repair, and meniscus root reconstruction. Moreover, compared with meniscectomy or meniscal repair, some evidence indicates that meniscal root reconstruction can be performed to reestablish the normal biomechanics of the knee [5].…”
Section: Introductionmentioning
confidence: 99%